A call for a standardized definition of perforated appendicitis - Rogers, Andrew P. (J Pediatr Surg, 2016)
BACKGROUND: Abscess rates have been reported as low as 1% and as high as 50% following perforated appendicitis (PA). This range may be due to lack of universal definition for PA. An evidence-based definition (EBD) is crucial for accurate wound classification, risk-stratification, and subsequent process optimization. ACS NSQIP – Pediatric guidelines do not specify adefinition of PA. We hypothesize reported post-operative abscess rates underrepresent true incidence, as they may include low-risk cases in final calculations. METHODS: Local institutional records of PA patients were reviewed to calculate the post-operative abscess rate. The ACS NSQIP – Pediatric participant use file (PUF) was used to determine cross-institutional post-operative abscess rates. A PubMed literature review was performed to identify trials reporting PA abscess rates, and definitions and rates were recorded. RESULTS: 20.9% of our patients with PA developed a postoperative abscess. The ACS NSQIP – Pediatric abscess rate was significantly lower (7.61%, p<0.001). In the eighteen published studies analyzed, average abscess rate (14.49%) was significantly higher than ACS NSQIP – Pediatric (p< 0.001). There was significantly more variation in trials that do not employ an EBD of perforation (Levene’s test F-value = 6.980, p = 0.018). CONCLUSIONS: A standard EBD of perforation leads to lower variability in reported post-operative abscess rates following PA; nonstandard definitions may be significantly altering the aggregate rate of post-operative abscess formation. We advocate for adoption of a standard definition by all institutions participating in ACS NSQIP – Pediatric data submission.